Ідентифікація ARS-послідовності флавіногенних дріжджів Pichia guilliermondii - Вороновський, А.Я.; Борецький, Ю.Р. (Биополимеры и клетка, 2000)
An autonomously replicating sequence adjacent to the RfBl gene encoding GTP cyclohydrolase II of the yeast Pichia guilliermondii was identified by transformation experiments. Detailed sequence analysis unveiled two potential ARS elements located 5' and 3' of the RIBI open reading frame. The chromosomal fragment containing the ARS-like sequence 3' to the RIBI structural gene, called PgARS, conferred autonomous replication to hybrid plasmids and high transformation frequencies (104 –105 transformants/ug DNA) in Pichia guilliermondii. Based on the PgARS element a series of E. coli–P. guilliermondii shuttle vectors was developed.